1995
DOI: 10.1016/s0213-9111(95)71251-1
|View full text |Cite
|
Sign up to set email alerts
|

Mortalidad en trabajadores de la siderurgia del país vasco*

Abstract: Most of mortality studies among steelworkers pointed out an increased frequency on cancer mortality, above all by lung cancer, and, in a lower proportion, by cancers of digestive and genitourinary systems. In Spain mortality rates are not published by occupation and economic activity to contrast these observations. It was carried out a proportionate mortality study among active or retired workers from an steel mill, Altos Hornos de Vizcaya, died from 1986 to 1993, to make a preliminary death risk assessment as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Another proportional mortality study was done among steelworkers who died between 1986 and 1993 in the Basque country (the Altos Hornos de Vizcaya steel mill) (22). Results showed a statistically significant excess of stomach cancer and renal cancer, as other authors have found.…”
Section: Ecologic and Death Certificate Studiesmentioning
confidence: 61%
“…Another proportional mortality study was done among steelworkers who died between 1986 and 1993 in the Basque country (the Altos Hornos de Vizcaya steel mill) (22). Results showed a statistically significant excess of stomach cancer and renal cancer, as other authors have found.…”
Section: Ecologic and Death Certificate Studiesmentioning
confidence: 61%